Virtual water and soy water footprint: increasing exports in Brazilian Amazon ports versus environmental and water risks (Research, Society and Development, 2023)
New concepts have been used to understand the multiple uses of water, an example of which is the study of virtual water and the water footprint, which can be used as indicators of efficient water use. The objective of this work was to analyze the volume of virtual water exported through the soy commodity by the ports of Arco Norte (Santarém-PA, Barcarena-PA and Itacoatiara-AM) in the period from 2015 to June 2020, and to relate the water footprint of soy in the Santarém-PA region. A large volume of virtual water is exported annually to other countries, the soybean crop is one of the crops that has been growing in Brazil, coming to the north, in the Amazon region where water resources are abundant, thus collaborating with the flow international virtual water facility. The advance of the loss of the biome can have climatic consequences, as this biome is responsible for supplying water vapor to the south and southeast of Brazil, favoring rainfall in this region, thus, an imbalance in the water resources of Brazil is possible.